Reconsidering Water Electrolysis: Producing Hydrogen at Cathodes Together with Selective Oxidation of n‐Butylamine at Anodes. Issue 24 (22nd November 2017) - Xue, Song; Watzele, Sebastian; Čolić, Viktor; Brandl, Kurt; Garlyyev, Batyr; Bandarenka, Aliaksandr S.
Abstract: Electrocatalysis for the oxygen evolution reaction (OER) is of great interest for improving the effectiveness of water splitting devices. Decreasing the anodic overpotential and simultaneously changing the anodic reaction selectively to produce valuable chemicals instead of O2 would be a major improvement of the overall cost efficiency. Some amines, when present in aqueous electrolytes, were recently shown to change the selectivity of the anodic process to generate H2 O2 rather than O2 on MnO x at pH 10. This results in unusually high apparent "anodic activities". In this work, industrially relevant OER catalysts, oxyhydroxides of cobalt (CoO x ), nickel–iron (NiFeO x ), and nickel (NiO x ) all show more pronounced effects. Moreover, as anodes they also selectively catalyzed the production of n butyronitrile from n ‐butylamine at higher pH as an easily retrievable valuable product. The pH dependence of the activity was investigated at pH values closer those at which alkaline electrolyzers operate. The highest activities were observed for NiO x thin‐film electrodes at pH 12 in the presence of 0.4 m n ‐butylammonium sulfate, without poisoning the active sites of Pt electrocatalysts at the hydrogen evolution electrode. 1 H NMR spectroscopy showed that n ‐butylamine is selectively oxidized to n ‐butyronitrile, an organic chemical with numerous applications. However, measurements using rotating ring‐disk electrodes indicated that some H2 O2 is also generated at the surface of the oxide anodes. Abstract : Twice the value : In electrocatalytic water splitting devices, decreasing anodic overpotential and simultaneously changing the anodic reaction to produce valuable chemicals instead of O2 would be a major improvement in overall cost efficiency. Oxyhydroxides of cobalt, nickel/iron, and nickel are industrially relevant electrocatalysts that, as anodes, can selectively catalyze the production of n ‐butyronitrile from n ‐butylamine as an easily retrievable valuable product.